Selling God [videorecording (DVD)] - Christman, Carl; Gilmad, Bruce; Chomsky, Noam (Breaking Glass Pictures, 2011)
What is the price of a soul? At a time when televangelists can fill a stadium at the same rate as a rock star and a theme park can sell tickets to the Holy Land, organized religion has in many ways put a price tag on salvation. Selling God is a fascinating and always-amusing survey of evangelical Christianity -- from Biblical times to the rise of mega churches to the post-9/11 culture wars. Combining historical insight with irreverent humor, director Carl Christman explores the many absurdities that arise when pop culture meets religious doctrine.